Communicative Functions in Children Raised in Three Different Social Contexts in Colombia: The Key Issue of Joint Attention - Moreno, Mayilín; Thommen, Evelyne; Morán, Elianne; Guidetti, Michèle (Frontiers in Psychology, 2021)
Children's sociocultural experiences vary around the world. Colombia is a South American country where the differences between socioeconomic statuses (SES) are huge. In this study, through the ECSP-E Scale, translated to Spanish and validated for linguistic and cultural equivalence, the development of three communicative functions were evaluated through an interactive sociopragmatic approach, in 36 24-month-old children, raised in three different social contexts in Colombia, with the goal of comparing them across groups of SES. The lowest SES group sample subjects were representative of extreme poverty and members of an ethnic group, the Wayuú’s. Results for the communicative functions, namely: social interaction (SI), joint attention (JA) and behavior regulation (BR), showed that the only function with no significant differences across SES was Joint Attention, supporting the hypothesis that the development of this function may be universal, in light of the fact that the Wayuú not only differed in their socioeconomic status but also in their culture from other subjects. Higher SES was related to better social interaction, while Low SES exhibit better behavior regulation than their High SES peers. Consequently, results are discussed considering socioeconomic and cultural differences in the development of communication and social interactions, leading us to reexamine the paradigms, theories and practices that are used when observing children raised in very poor environments.